2016
DOI: 10.1002/bbb.1708
|View full text |Cite
|
Sign up to set email alerts
|

Scaling up bioethanol production from the farmed brown macroalga Macrocystis pyrifera in Chile

Abstract: Interest in third‐generation biomass such as macroalgae has increased due to their high biomass yield, absence of lignin in their tissues, lower competition for land and fresh water, no fertilization requirements, and efficient CO2 capture in coastal ecosystems. However, several challenges still exist in the development of cost‐effective technologies for processing large amounts of macroalgae. Recently, genetically modified micro‐organisms able to convert brown macroalgae carbohydrates into bioethanol were dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 41 publications
0
22
0
Order By: Relevance
“…In this case, we are utilizing two organisms with different optimal temperatures for growth thus implying culture temperature as an important parameter in co-culture performance. To this end, we explored the impacts of varying fermentation temperature (25,30,33.5 and 37 °C), time (20, 48, and 72 h), and initial inoculation ratio of engineered strains (100:1, 10:1, 1:1, 1:10 to 1:100) in a large-scale test tube system ( Fig. 3 and Additional file 1: Fig.…”
Section: Investigating the Impacts Of Inoculation Ratio And Fermentatmentioning
confidence: 99%
“…In this case, we are utilizing two organisms with different optimal temperatures for growth thus implying culture temperature as an important parameter in co-culture performance. To this end, we explored the impacts of varying fermentation temperature (25,30,33.5 and 37 °C), time (20, 48, and 72 h), and initial inoculation ratio of engineered strains (100:1, 10:1, 1:1, 1:10 to 1:100) in a large-scale test tube system ( Fig. 3 and Additional file 1: Fig.…”
Section: Investigating the Impacts Of Inoculation Ratio And Fermentatmentioning
confidence: 99%
“…The second 24 h process used an oligoalginate-lyase to break all oligo-alginates into monomers. Ammonia was added in solution which spontaneously converts 4-deoxy-L-erythro-5-hexoseulose urinate (DEHU), an alginate monomer to 5-hydroxypyridine-2-carboxylic acid (5-HPA) which could be detected and quantified on HPLC/UV (for detailed protocols see [35]).…”
Section: Chemical Characterizationmentioning
confidence: 99%
“…Pilot-production has demonstrated that 124 wet ton.ha -1 of M. pyrifera can be achieved using wild individuals to seed ropes for suspended systems [32]. The development of M. pyrifera aquafarming is expected to emerge rapidly for several reasons: established procedures for cultivation in hatcheries [33] and open ocean [32] allow for the testing of the agronomic performance of a large array of genotypes and pilot scale production; technology used to convert biomass to bioethanol implemented at the pilot scale [34,35]; and identification of novel components for food and pharmaceutical uses that add value to the biomass production [5,36,37]. M. pyrifera is considered to be a highly plastic species [38,39], yet some morphological traits were considered to express a strong phylogenetic signal.…”
Section: Introductionmentioning
confidence: 99%
“…In Western countries, kelp species (primarily the sugar kelp, Saccharina latissima and winged kelp, Alaria esculenta) have been cultivated during the last two decades in the North Atlantic Ocean (e.g., the United States, Canada, Iceland, Norway, Scotland, Ireland, Sweden, and Germany, etc.) (Buck and Buchholz 2004, Barrington et al 2009, Broch et al 2013, Kraemer et al 2014, Kim et al 2015b, Marinho et al 2015 and Macrocystis, Saccharina latissima, and Alaria esculenta in the eastern Pacific Ocean (e.g., Chile: Buschmann et al 2008b, 2014, Camus et al 2016, Correa et al 2016, Valero et al 2017; Alaska: Stekoll and Peeples 2016). The kelp aquaculture industry in the western countries has become one of the fastest growing industries (Cottier-Cook et al 2016).…”
Section: Kelp (Saccharina and Undaria)mentioning
confidence: 99%